Incidence and Predictive Risk Factors of Infective Events in Patients With Multiple Sclerosis Treated With Agents Targeting CD20 and CD52 Surface Antigens. (21st October 2019) - Zappulo, Emanuela; Buonomo, Antonio Riccardo; Saccà, Francesco; Russo, Cinzia Valeria; Scotto, Riccardo; Scalia, Giulia; Nozzolillo, Agostino; Lanzillo, Roberta; Tosone, Grazia; Gentile, Ivan
Abstract: Objective: Monoclonal antibodies (MAbs) directed against the CD20 and CD52 antigens are used increasingly in patients with multiple sclerosis (MS). Several life-threatening opportunistic infections have been reported in postmarketing case series. The aim of this study was to investigate the incidence of infections and associated prognostic factors during the first year of treatment in patients receiving anti-CD20 (ocrelizumab or rituximab) or anti-CD52 MAbs (alemtuzumab). Methods: A retrospective study was conducted in patients with MS referring to the Neurodegenerative Diseases Center at the University of Naples Federico II who received MAbs between November 2015 and June 2018. Results: A total of 163 patients were enrolled. Approximately 40% of patients experienced lymphocytopenia during treatment. Eighty-six infective events were reported in 67 patients (41%). Bacterial infections were significantly more frequent with anti-CD20, whereas viral infections prevailed with alemtuzumab. Cytomegalovirus reactivation rates were significantly higher in the alemtuzumab group than in patients on anti-CD20 (51% vs 6%, P < .001). The overall annualized infection rate was 1.1 per patient-year, higher in patients on anti-CD52 versus those on anti-CD20 regimens (1.5 vs 0.8 per patient-year). Alemtuzumab treatment, prior exposure to ≥2 MS drugs, and iatrogenic immune impairment significantly and independently predicted an infection event (adjusted hazard ratio [aHR], 2.7; P = .013; aHR, 1.7; P = .052; and aHR, 2.9; P = .004; respectively). Conclusions: Given their considerable infection risk, MS patients receiving MAbs should undergo timely follow up and tailored preventive interventions. Anti-CD52–based treatment, prior exposure to MS drugs, and on-treatment immune impairment are significant predictive factors of infection and their evaluation could help clinicians to stratify a patient's risk of infection. Abstract : A high incidence of infections was observed in patients with multiple sclerosis (MS) receiving anti-CD20 and -CD52 agents. Cytomegalovirus reactivation rates were particularly high in Alemtuzumab-treated patients. Alemtuzumab treatment, prior exposure to MS drugs, and iatrogenic immune impairment were identified as independent risk factors for infections.